EKSPLORASI Actinomycetes SEBAGAI KANDIDAT ANTIBAKTERI PATOGEN YANG RESISTEN DARI RHIZOSFER TUMBUHAN LEDA (Eucalyptus deglupta Blume.) DI TAMAN NASIONAL LORE LINDU, INDONESIA: Abstract - Alwi Millang (Biocelebes, 2020)
Actinomycetes that live in the rhizosphere of the Leda plant (Eucalyptus deglupta Blume.) Have the potential to produce pathogenic antibacterial compounds in humans. The ecosystems thought to be inhabited by Actinomycetes that produce pathogenic antibacterial compounds in humans is the rhizosphere of Leda endemic plant in the Lore Lindu National Park, Central Sulawesi. The purpose of this study was to isolate various isolates of Leda plant rhizosphere Actinomycetes in TNLL as a producer of pathogenic antibacterial compounds in humans. This research is divided into several stages. The first stage was sampling, isolation, and screening of Actinomycetes producing human pathogenic antibacterial compounds. Rhizosphere soil samples were taken by purposive sampling method combined with the quadrant method by measuring various environmental factors. The second stage is a selection to analyze the potential and efficacy of Actinomycetes isolates as producing antibacterial compounds against pathogenic bacteria in humans. The results showed that the condition of Leda plant vegetation in the Anaso-Rorekatimbu area was generally the same for each spot and supported the presence of Actinomycetes. The density of Actinomycetes is relatively the same for each spot. As many as 15 isolates were isolated from the Leda rhizosphere of Actinomycetes. Based on spore morphological and biochemical characterization, the 15 isolates were included in the Genus Streptomyces. Actinomycetes isolates L213, L433, and L411 were the most potent isolates and had broad-spectrum inhibition, because they were able to inhibit the four test bacteria S. aureus, MRSA, V. cholera, and EPEC. Keywords: Actinomycetes, Eucalyptus deglupta Blume., and pathogenic antibacterial